The Improving of the Students Learning Outcomes Junior High School with the Application of the Project Based Learning Blended Think Pair Share: Peningkatan Hasil Belajar Peserta Didik Sekolah Menengah Pertama dengan Penerapan Project Based Learning Dipadukan Think Pair Share - Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2022)
The students need the scientific competence through the subjectmatter in the subject study and mastery of information technology in the era ofsociety 5.0, because of that it is necessary to apply the learning model. Thepurposes this research to apply the Project Based Learning (PjBL) blended theThink Pair Share (TPS) as the solution that aims to find out the description ofthe application of this model that can be used as the learning option in theschool. The research method used is the qualitative descriptive method. Theimplementation of the research in the Junior High School (SMP)Muhammadiyah 2 Taman Sidoarjo in the IX B class with the 25 students forthe Magnetism and Its Use in the Technological Products topic, while theresults of the study indicate that the activities of this learning stage are carriedout well by the students and teachers, the students have the average responsesof the motivation = 3.75 and interest = 3.53 and with good category on thelearning, as well as the completeness learning shows of the proportional index(P) classical = 0.88 ≥ 0.85 with the complete and finishedlearning category, it means that classical mastery isachieved so that it can improve the students learningout comes well, such as: a) to increase the motivationand interest on the learning, b) to improve theindividual and classical learning outcomes, c) toimprove the problem solving abilities, d) to improve theskills in the managing information resources, e) toimprove the critical and higher order thinking skills,and f) when the students learn and work with the partnergroups, they find and gain the skills relate to plan,organize, negotiate, the party responsible for the taskthat they get, and how the information will be collectedfor the presentation in front of the class.